2018
DOI: 10.3390/toxics6030056
|View full text |Cite
|
Sign up to set email alerts
|

Monthly Variations in Perfluorinated Compound Concentrations in Groundwater

Abstract: Large-scale manufacturing of poly- and perfluorinated compounds in the second half of the 20th century has led to their ubiquity in the environment, and their unique structure has made them persistent contaminants. A recent drinking water advisory level issued by the United States Environmental Protection Agency lowered the advisory level concentration of perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) from 200 nanograms per liter and 400 nanograms per liter, respectively, to 70 nanograms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Substitution of hydrogen with fluorine in organic molecules affects their chemical and physical properties, e.g., increased chemical and thermal stability and/or oleophobic as well as hydrophobic properties [ 1 , 2 ]. These molecules are described according to Buck et al as per- and polyfluorinated alkyl substances (PFASs) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of hydrogen with fluorine in organic molecules affects their chemical and physical properties, e.g., increased chemical and thermal stability and/or oleophobic as well as hydrophobic properties [ 1 , 2 ]. These molecules are described according to Buck et al as per- and polyfluorinated alkyl substances (PFASs) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been few studies investigating temporal trends of PFAS in groundwater or PFAS transport across surface-water/groundwater boundaries. Steele et al 60 found no statistically signicant temporal trend in groundwater data from a site in Alaska, but did nd (weakly) statistically signicant temporal trends for groundwater at Pease Air Force Base in New Hampshire. Our results indicate stronger seasonal trends, likely owing to the surface-water/groundwater boundary investigated in this work.…”
Section: View Article Onlinementioning
confidence: 96%